Relationship between social activities and cognitive impairment in Chinese older adults: the mediating effect of depressive symptoms - Yang, Qianke; Lin, Shichong; Zhang, Zhuyun; Du, Shuhao; Zhou, Dan (Frontiers in Public Health, 2025)
BackgroundThe differential impacts of various social activities on dementia prevention and the mediating role of depression in this relationship remain unclear.ObjectivesThis study aimed to identify the effects of different social activities on cognitive function, examine the mediating role of depression, and provide evidence for targeted interventions to prevent cognitive decline.MethodsUsing data from CHARLS, we employed RCS analysis and Structural Equation Modeling to examine the relationships between social activities, depression, and cognitive function in older adults.ResultsSocial activity participation is non-linearly inversely related to both cognitive impairment and depression risk. Cognitive function and social activities were significantly mediated by depression. Cognitively stimulating and physically stimulating activities had the greatest positive effects on mental health.ConclusionOur findings highlight the complex interplay between social engagement, depression, and cognitive health in aging. They support developing targeted interventions promoting physical and cognitive social activities to maintain cognitive function and reduce depression risk in older adults, potentially alleviating the burden of cognitive impairment in aging populations.